Thermodynamic weirdness - Lemons, Don S. (The MIT Press, 2019)
Inventing temperature – Heat and caloric – Carnot's analysis – Absolute temperature – Mechanical equivalent of heat – First law of thermodynamics – Second law of thermodynamics – Absolute temperature, again – Entropy – Law of entropy non-decrease – The fate of the universe? – Classical thermodynamics
Includes bibliographical references and index
Keywords: Thermodynamics